蛋黄脂质粉末油脂制备工艺优化及性质研究Optimization of preparation process and properties of egg yolk lipids powdered oil - 蔡芸丹1，2，饶胜其3，顾璐萍1，2，常翠华1，2，李俊华1，2，杨严俊1，2，苏宇杰1，2 CAI Yundan1,2，RAO Shengqi3，GU Luping1,2，CHANG Cuihua1,2， LI Junhua1,2, YANG Yanjun1,2, SU Yujie1,2 (Zhongguo youzhi)
为解决蛋黄脂质容易氧化的问题，采用微胶囊技术制备蛋黄脂质粉末油脂，通过单因素实验研究壁材种类、壁芯比、蔗糖脂肪酸酯添加量、均质压力和均质次数对乳液乳化稳定性和蛋黄脂质粉末油脂包埋率的影响，确定蛋黄脂质粉末油脂的最佳制备工艺，并探究蛋黄脂质制取方法（乙醇萃取、超临界CO2萃取、超临界CO2萃取-脱胆固醇）对粉末油脂理化性质的影响。结果表明：以超临界CO2萃取法制取的蛋黄脂质为芯材，麦芽糊精、玉米变性淀粉和乳清蛋白为壁材，蛋黄脂质粉末油脂的最佳制备工艺为麦芽糊精与玉米变性淀粉质量比5∶ 1、乳清蛋白添加量（以壁材质量计）5%、壁芯质量比4∶ 1、蔗糖脂肪酸酯添加量（以壁材质量计）3%、均质压力40 MPa、均质次数3次，在此条件下乳液乳化稳定性达到85.88%，蛋黄脂质粉末油脂包埋率达到93.70%。在最佳条件下制备3种蛋黄脂质粉末油脂，其中超临界CO2萃取法制取的蛋黄脂质的粉末油脂水分含量较低、流动性好，颗粒呈完整的球形结构，多不饱和脂肪酸含量较高，且其储藏稳定性明显优于乙醇萃取法的。综上，超临界CO2萃取法制取的蛋黄脂质的粉末油脂具有较高的包埋率和良好的稳定性，更适合作为粉末油脂的脂质原料。 In order to solve the problem of easy oxidation of egg yolk lipids, egg yolk lipids powdered oil was prepared by microencapsulation technology, the effects of parameters such as wall material type, wall-core mass ratio, sucrose fatty acid esters dosage, homogenization pressure and homogenization times on the emulsion stability and embedding rate of egg yolk lipids powdered oil were investigated by single factor experiments to determine the optimal preparation process of the powdered oil, and the effects of different ways of egg yolk lipids preparation (ethanol extraction, supercritical CO2 extraction, supercritical CO2 extraction-cholesterol removal) on the physicochemical indexes of the powdered oil were explored. The results showed that egg yolk lipids extracted by supercritical CO2 extraction were used as the core material, and maltodextrin, modified corn starch and whey protein were used as the wall material, the optimal preparation process of egg yolk lipids powdered oil was determined as follows: mass ratio of maltodextrin to modified corn starch 5∶ 1, whey protein dosage (in terms of wall material amount) 5%, wall-core mass ratio 4∶ 1, sucrose fatty acid esters dosage (in terms of wall material amount) 3%, homogenization pressure 40 MPa, and homogenization times 3. Under these conditions, the stability of the emulsion reached 85.88%, and the embedding rate of the powdered oil reached 93.70%. Three kinds of egg yolk lipids powdered oil were prepared under the optimal preparation conditions, in which the powdered oil of egg yolk lipids extracted by supercritical CO2 extraction had lower moisture content, good fluidity, intact spherical structure of the particles, high content of polyunsaturated fatty acids and higher storage stability than that of the ethanol extraction method. In conclusion, the powdered oil of egg yolk lipids obtained by supercritical CO2 extraction has a high embedding rate and good stability, which is more suitable as the lipid feedstock of powdered oil.